2022
DOI: 10.3390/biomedicines10051187
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles Loaded with Docetaxel and Resveratrol as an Advanced Tool for Cancer Therapy

Abstract: A growing interest in the use of a combination of chemosensitizers and cytostatics for overcoming cancer resistance to treatment and the development of their delivery systems has been observed. Resveratrol (Res) presents antioxidant, anti-inflammatory and chemopreventive properties but also limits multidrug resistance against docetaxel (Dtx), which is one of the main causes of failure in cancer therapy with this drug. However, the use of both drugs presents challenges, including poor bioavailability, the unfav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 155 publications
3
29
0
Order By: Relevance
“…Thus, it is suggested that new methods of intelligent drug delivery should be used in addition to targeting the hub genes obtained in this study to achieve the effective performance of combination therapy with these two types of agents. For example, a study illustrated that nanoparticles loaded with docetaxel and resveratrol made HER-2-positive breast cancer cells sensitive to docetaxel [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is suggested that new methods of intelligent drug delivery should be used in addition to targeting the hub genes obtained in this study to achieve the effective performance of combination therapy with these two types of agents. For example, a study illustrated that nanoparticles loaded with docetaxel and resveratrol made HER-2-positive breast cancer cells sensitive to docetaxel [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oral resveratrol administration has been found to help prevent colon cancer in people [ 306 ]. In addition, the FDA has approved a clinical trial for gastrointestinal tumors (NCT01476592) [ 371 ]. The effect of resveratrol on notch-1 signaling, the effect on patient therapy, and patient toleration of resveratrol administration were all examined throughout this trial.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…The effect of resveratrol on notch-1 signaling, the effect on patient therapy, and patient toleration of resveratrol administration were all examined throughout this trial. It was discovered that resveratrol injection enhanced cleaved caspase-3 levels in malignant tissue, implying that apoptosis in cancer cells was boosted [ 371 ].…”
Section: Clinical Studiesmentioning
confidence: 99%
“…The nanoparticle delivery systems improve the aqueous solubility of DTX and increase its tissues selectivity through passive and active targeting, which subsequently enhances the antitumor effect and alleviates sides effects on normal tissues. Some DTX-based nanoparticles such as albumin-bound DTX (ABI-008), LE-DT, and BIND-014 failed in clinical trials (He et al., 2019 ; Zhang et al., 2019 ; van Eerden et al., 2020 ; Jurczyk et al., 2022 ). The formulation of LE-DT was prepared by electrostatic interaction, of which negatively charged synthetic phospholipids and cholesterol and drugs with opposite charge formed stable liposomes (Zhang et al., 2019 ; Jurczyk et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some DTX-based nanoparticles such as albumin-bound DTX (ABI-008), LE-DT, and BIND-014 failed in clinical trials (He et al., 2019 ; Zhang et al., 2019 ; van Eerden et al., 2020 ; Jurczyk et al., 2022 ). The formulation of LE-DT was prepared by electrostatic interaction, of which negatively charged synthetic phospholipids and cholesterol and drugs with opposite charge formed stable liposomes (Zhang et al., 2019 ; Jurczyk et al., 2022 ). BIND-014 is composed of DTX encapsulated in a polymer core made of a hydrophobic poly(lactide) surrounded by a hydrophilic poly(ethylene glycol) conjugated with a small molecule of prostate-specific membrane antigen (PSMA)-targeting ligands (Jurczyk et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%